2009
DOI: 10.1101/lm.1041309
|View full text |Cite
|
Sign up to set email alerts
|

Extinction circuits for fear and addiction overlap in prefrontal cortex

Abstract: Extinction is a form of inhibitory learning that suppresses a previously conditioned response. Both fear and drug seeking are conditioned responses that can lead to maladaptive behavior when expressed inappropriately, manifesting as anxiety disorders and addiction, respectively. Recent evidence indicates that the medial prefrontal cortex (mPFC) is critical for the extinction of both fear and drug-seeking behaviors. Moreover, a dorsal-ventral distinction is apparent within the mPFC, such that the prelimbic (PL-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

39
642
5
5

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 661 publications
(697 citation statements)
references
References 194 publications
39
642
5
5
Order By: Relevance
“…Our observation that Fos activation was greater in the infralimbic than prelimbic cortex of adult rats during heroin-seeking is consistent with a greater role for the infralimbic than prelimbic region in heroin-seeking (Van den Oever et al, 2008;Bossert et al, 2011), but contradicts theories based mainly on cocaine-related behavior that the infralimbic cortex inhibits drug-seeking, whereas the prelimbic cortex promotes it (Peters et al, 2009). For both subregions, we also observed activation in only a small percentage of neurons during heroin-seeking, similar to the 5-7% activation reported previously (Bossert et al, 2011).…”
Section: Discussionsupporting
confidence: 45%
“…Our observation that Fos activation was greater in the infralimbic than prelimbic cortex of adult rats during heroin-seeking is consistent with a greater role for the infralimbic than prelimbic region in heroin-seeking (Van den Oever et al, 2008;Bossert et al, 2011), but contradicts theories based mainly on cocaine-related behavior that the infralimbic cortex inhibits drug-seeking, whereas the prelimbic cortex promotes it (Peters et al, 2009). For both subregions, we also observed activation in only a small percentage of neurons during heroin-seeking, similar to the 5-7% activation reported previously (Bossert et al, 2011).…”
Section: Discussionsupporting
confidence: 45%
“…The infralimbic cortex controls cueinduced reinstatement of drug-seeking behavior following extinction (Peters et al, 2008;LaLumiere et al, 2012). In fact, this region has been proposed as a key component of the 'stop circuit' substrate mediating the transition from regulated to compulsive drug use (Kalivas, 2008;Peters et al, 2009). We are currently investigating the consequences of disrupted development of dopamine connectivity on the structure and function of infralimbic pyramidal neurons and on behaviors that are linked to infralimbic cortical function.…”
Section: Dcc-mediated Effects Of Amphetamine On the Sculpting Of Mpfcmentioning
confidence: 99%
“…Strikingly, we found that synaptic Bcan protein levels following exposure to heroin-conditioned cues were equivalent to the saline control group, indicating that cue-induced reinstatement of heroin seeking resulted in a rapid recovery of Bcan in the mPFC. Glutamatergic projections from the mPFC to the striatum have a critical role in reinstatement of drug seeking LaLumiere and Kalivas, 2008;Peters et al, 2009). Therefore, we determined whether Bcan and Tnr were also regulated in the NAc and dorsal striatum (Figure 4b and c).…”
Section: Confirmation Of Regulation By Immunoblotting and Real-time Qmentioning
confidence: 99%